Effect Of Asset Intensity, Intellectual Capital, And Leverage On Sticky Cost : Empirical Study On Industrial Sector Manufacturing Companies Listed - Tasykiylah Nuril Maulidiyah; Lailatus Sa’adah (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This research investigates the influence of several factors on cost stickiness, including asset intensity, intellectual capital, and leverage, in manufacturing firms from the industrials sector listed on the Indonesia Stock Exchange over the 2020–2024 period. Methodology: An associative quantitative approach is employed using annual time-series data from nine companies obtained from the official IDX website. Panel data regression is applied as the main analytical technique. Results: Results of asset intensity on sticky cost shows a probability value of 0.3762 > 0.05. Intellectual capital on sticky cost yields a probability value of 0.4976 > 0.05. Leverage on sticky cost shows a probability value of 0.0114 < 0.05. Findings: The findings indicate that leverage significantly affects cost stickiness in partial testing, whereas asset intensity and intellectual capital show no significant effect. Novelty: This study contributes to the cost stickiness literature by providing empirical evidence from the Indonesian industrials manufacturing sector during the post-pandemic period (2020–2024), a context that remains underexplored in prior studies. Originality: Originality of this research is taken from manufacturing companies in the industrials sector. Conclusion: Conclusion imply that other factors beyond those examined in this study may play an important role in determining cost stickiness.Type of Paper: This paper is Empirical Case Study a researchpaper.